Kinetic Study of the Aluminum–water Reaction Using NaOH/NaAlO2 Catalyst for Hydrogen Production from Aluminum Cans Waste - Fadhilah, Nur; Muharja, Maktum; Risanti, Doty Dewi; Wahyuono, Ruri Agung; Satrio, Dendy; Khamil, Achri Isnan; Fadilah, Siska Nuri (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
The presence of oxide layers covering the surface of aluminum is known to impede the hydrogen production reaction. These oxide layers can be broken by adding catalysts and increasing the aluminum-water reaction temperature. Common catalysts used are alkaline catalysts that are capable of achieving high hydrogen production rates in a short time at lower temperatures, while intermediate temperatures of above 50 °C can accelerate the hydration reaction of the oxide layer. Herein, the mixture of NaOH and NaAlO2 catalysts was employed to attain a stable NaAlO2 solution and continuous reaction of NaOH and aluminum. This research analyzes the influence of temperature between 32 and 80 °C on the aluminum, 0.3 M NaOH and 0.001 M NaAlO2 catalysts solution at atmospheric pressure. All solutions produces a similar hydrogen yields and rate. Solutions containing NaAlO2 indicate reverse reaction that surpressing the Al(OH)3 precipitation. Residue from the reaction is investigated using X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), and Scanning Electron Microscope (SEM). The volume of hydrogen produced is evaluated using a mathematical mass reduction and shrinking core model. The rate of hydrogen production depends largely on the aqueous solution's temperature, with an activation energy of 47.4 kJ/mol. Based on the findings, it is readily apparent that the reaction only produced gibbsite and bayerite, with gibbsite and bayerite being dominant at 32–70 °C and 80 °C, respectively. The mass reduction model fits well with the present results with only an average 5.1 mL deviation, whereas the shrinking core model generally tends to result in underestimated values with an average deviation of 23.9 mL. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).